Neutron Diffraction Study of the Martensitic Transformation of Ni2.07Mn0.93Ga Heusler Alloy - Lara Righi (MDPI AG, 2021)
The martensitic transition featuring the ternary Heusler alloy Ni2.09Mn0.91Ga was investigated by neutron diffraction. Differential scanning calorimetry indicated that structural transition starts at 230 K on cooling with a significant increase in the martensitic transformation onset compared to the classical Ni2MnGa. The low-temperature martensite presents the 5M type of modulated structure, and the structural analysis was performed by the application of the superspace approach. As already observed in Mn-rich modulated martensites, the periodical distortion corresponds to an incommensurate wave-like shift of the atomic layers. The symmetry of the modulated martensite at 220 K is orthorhombic with unit cell constants a = 4.2172(3) Å, b = 5.5482(2) Å, and c = 4.1899(2) Å; space group Immm(00γ)s00; and modulation vector q = γc* = 0.4226(5)c*. Considering the different neutron scattering lengths of the elements involved in this alloy, it was possible to ascertain that the chemical composition was Ni2.07Mn0.93Ga, close to the nominal formula. In order to characterize the martensitic transformation upon increasing the temperature, a series of neutron diffraction patterns was collected at different temperatures. The structural analysis indicated that the progressive change of the martensitic lattice is characterized by the exponential change of the c/a parameter approaching the limit value c/a = 1 of the cubic austenite.